Collections / National Gallery of Canada - National Gallery of Canada (2006)
[Dt.:] Die National Gallery of Canada (Musée des beaux arts du Canada) in Ottawa verfügt über eine umfangreiche Sammlung von Gemälden, Zeichnungen, Skulpturen und Fotografien. Der Schwerpunkt liegt vor allem auf kanadischer Kunst. Die Sammlung ist über den Online-Katalog suchbar. - [Engl.:] The National Gallery of Canada (Musée des beaux arts du Canada), located in the capital city Ottawa, Ontario, has a large and varied collection of paintings, drawings, sculpture and photographs. Although its focus is on Canadian art, it holds works by many noted European artists. The collection is searchable in the online-database.